Appendico-ileal knotting mimicking adhesive bowel disease - Okello, M.; Kharono, B.; Mwaka, E.; Lock, G. (Zeitschrift für Gastroenterologie, 2016)
Appendico-ileal knotting is a very rare and widely unknown cause of closed loop bowel obstruction. In most cases it is discovered incidentally during surgery. We report a 59 year old female with a previous history of a total abdominal hysterectomy who presented with features of intestinal obstruction and was thought to suffer from postoperative adhesions. At laparotomy, appendico-ileal knotting was found; after appendectomy, she made a full recovery. Appendico-ileal knotting should be known as a possible differential diagnosis when managing patients with features of intestinal obstruction and symptoms or signs of appendicitis.
Keywords: Appendizitis; Appendix-Ileum-Verknotung; Appendix-Band-Syndrom; Adhäsionen